Ecología sociocultural de los estudiantes de Antropología de la Universidad Nacional del Centro del Perú - Mendoza Mesías, Leonardo Carlos (2017)
This is a research carried out during the year 2017 in the campus. The problem identified has to do with the influence of cultural ecology in the academic environment of the students from the faculty of Anthropology from the Universidad Nacional del Centro del Perú, that is, what the way they adapt socioculturally to their environment is, what the strategies they apply daily are and how their relationship with their natural and social environment is. From this, the objective propounded was to analyze the manifestations of the sociocultural ecology practiced by the university students from the faculty of Anthropology in direct interaction with their natural and social environment through the application of their culture. The contribution of this study is to know the way students solve their social and environmental difficulties from the practice of their individual knowledge. The present study, more than an ethnographic research, only intends to be an exploratory research. The field method was the ethnographic one, putting special emphasis on participant observation supported by audiovisual and quantitative techniques such as the survey. The universe of research considered the students from the faculty of Anthropology, whose approximate total number was 370. A first observed result is that the students constitute an urban population group, academically formed by an age and social diversity, as well as biological and cultural very plural.   DOI: https://doi.org/10.31876/sl.v1i1.1